Influence of kinesiotherapy in water and on land to prevent violations of posture in children - Sitnikova N.S; Tsiplyaeva A.V (Kharkov National Pedagogical University, 2011)
Disclosed problems prevent incorrect posture in children with exercise in the water therapeutic swimming and Pilates. Developed and tested methodology which was aimed at restoring and improving spinal mobility impairments, respiratory system and retention of skill correct posture. Proved that when properly used kinesotherapy patients increased efficiency, activated natural systems to adapt, improve the state of the central and autonomic nervous system is stimulated by mental activity and improvement occurs.